Physicochemical characterisation of sunflower seed oil bodies ex-vivo - Fisk, Ian (2007)
Oilseeds store energy as triacylglycerides during periods of dormancy in preparation for germination and the early stages of development. The triacylglyceride is stored in discrete organelles termed oil bodies. Oil bodies are formed during the synthesis of neutral lipids within the bilayer of cellular endoplasmic reticulum (ER); as lipid is synthesised it forms droplets of oil that swell distending the ER membrane and at a critical diameter separate from the ER by vesiculation forming independent organelles. These organelles are structurally stabilised by a phospholipid monolayer originating from the ER and the addition of highly amphiphilic oleosin proteins.